Conceptual Understanding of Credit Risk Management and Portfolio Performance - Nyende, Kansiime Mary; Kasozi-Mulindwa, Saturninus (New Innovations in Economics, Business and Management Vol. 10, 2022)
The paper draws from findings of interviews conducted on purposively selected staff in the credit risk management function, including credit risk staff, Relationship Managers and Credit Officers across eight (8) commercial banks in Uganda. In addition, views of the staff of Bank of Uganda; the regulator as well as the Uganda Bankers Association; an umbrella organization of all commercial banks in Uganda were solicited. Uganda has long struggled with portfolio quality issues, which has resulted in a string of financial woes. Existing empirical evidence links portfolio performance to credit risk management, implying that credit risk management must be improved to increase portfolio performance. It assumes that credit risk management and portfolio performance have a linear connection. This research adds to the corpus of knowledge by delving deeper into the credit risk management process. It discovers potential interconnections at various phases of credit risk management. The credit risk management function needs to emphasize adjustment of the initial treatment mechanisms through more frequent loan monitoring, loan restructuring, relationship management and after sales financial literacy.